Occupational health risk assessment of manufacturing workers using the hand activity level method - Widodo, Silvi; Indrasari, Lolyka Dewi (International Journal of Industrial Optimization, 2026)
Repetitive manual handling tasks in industrial settings often expose workers to musculoskeletal risks, particularly when performed without ergonomic consideration. At PT. ABC, production workers are routinely engaged in lifting and assembling heavy components, raising concerns about their long-term health and safety. To address this issue, a structured assessment using the ACGIH TLV for Hand Activity Level (HAL) was conducted to evaluate biomechanical exposure and identify ergonomic risks. This study contributes by applying a quantitative, evidence-based framework to assess real workplace conditions and offer actionable insights for intervention. It also demonstrates how HAL and Borg CR-10 metrics can be integrated into practical ergonomic evaluations in industrial environments. The research involved five workers from the concrete production division. Data were collected through direct observation and video analysis to determine hand movement frequency and peak force levels. The HAL values and Borg CR-10 scores were used to calculate the Exposure Ratio (ER) for each worker, serving as the main indicator of ergonomic risk. Results revealed that all five workers had ER values ranging from 1.18 to 1.30, exceeding the ACGIH TLV threshold of 1.0. This indicates a consistently high risk for work-related musculoskeletal disorders (WMSDs). Frequent lifting of 12–13 kg loads combined with moderate-to-high hand activity and poor posture contributed to elevated strain levels. These findings confirm that the existing work system places employees at risk and highlight the need for immediate ergonomic improvements. Moreover, the HAL-ER assessment framework used in this study provides structured data that can be utilized in simulation-based planning or optimization models. By integrating these metrics into ergonomic redesign scenarios such as task reallocation, force-load balancing, or layout planning future studies can enhance both worker safety and operational efficiency.